OVERVIEW OF IRON STATUS IN CHRONIC KIDNEY DISEASE STAGE 5 PATIENTS UNDERGOING REGULAR HEMODIALYSIS: : A LITERATURE REVIEW - Setiawan MD, Daniel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
Decreased of haemoglobin (Hb) in patients with CKD almost occurs in 80% of cases. The causes are multifactorial, including deficiency of erythropoietin production, a circulating factor that appears to inhibit erythropoietin, shortened red blood cell half-life, increased gastrointestinal blood loss due to thrombocytopenia, folic acid and iron deficiency, and blood loss from hemodialysis or laboratory test samples. This literature evaluation drew its data from full-text English publications published in the preceding up to 2000 until 2022. This study discusses iron status in CKD stage 5 patients undergoing regular hemodialysis. We utilised the databases Sage Pub, Pubmed, and Google Schoolar to create this study. Research shows that serum iron and TIBC levels of patients with CKD who undergo maintenance hemodialysis are better than CKD patients without hemodialysis, but lower than healthy controls and those who undergo kidney transplantation. This figure is different for ferritin.